Microsphere-based optical frequency comb generator for 200 GHz spaced WDM data transmission system - Anashkina, Elena A.; Marisova, Maria P.; Andrianov, Alexey; Akhmedzhanov, Rinat A.; Murnieks, Rihards; Tokman, Mikhail D.; Skladova, Laura; Oladyshkin, Ivan; Salgals, Toms; Lyashuk, Ilya; Sorokin, Arseniy; Spolitis, Sandis; et al. (Photonics, 2020)
Optical frequency comb (OFC) generators based on whispering gallery mode (WGM) microresonators have a massive potential to ensure spectral and energy efficiency in wavelength-division multiplexing (WDM) telecommunication systems. The use of silica microspheres for telecommunication applications has hardly been studied but could be promising. We propose, investigate, and optimize numerically a simple design of a silica microsphere-based OFC generator in the C-band with a free spectral range of 200 GHz and simulate its implementation to provide 4-channel 200 GHz spaced WDM data transmission system. We calculate microsphere characteristics such as WGM eigenfrequencies, dispersion, nonlinear Kerr coefficient with allowance for thermo-optical effects, and simulate OFC generation in the regime of a stable dissipative Kerr soliton. We show that by employing generated OFC lines as optical carriers for WDM data transmission, it is possible to ensure error-free data transmission with a bit error rate (BER) of 4.5 × 10-30, providing a total of 40 Gbit/s of transmission speed on four channels.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dissipative Kerr soliton (DKS); Non-return-to-zero (NRZ); Optical frequency comb (OFC); Passive optical network (PON); Silica microsphere; Wavelength-division multiplexing (WDM); Whispering gallery mode resonator (WGMR)